Do gender identities of femininity and masculinity affect the intention to buy ethical products? - Pinna, Mariella (Psychology & marketing, 2020)
This study shows that gender identity affects ethical intentions. We investigate the intention to purchase ethical products through a survey study among young consumers in Italy. Measures of planned behavior, internal ethics, self‐identity, and moral harm, together with proxies for individual gender identities of femininity and masculinity are included in our model of intention to purchase ethically. Results show that femininity significantly increases ethical intent, whereas masculinity has an opposite effect. These findings are robust to gender. In fact, the relations of femininity and masculinity on the intention to consume ethical products hold when the subsamples of males and females are considered. This study relates to the ongoing debate regarding the determinants of ethical decision‐making and the feminine stereotype by extending the understanding of the attitude‐intention gap in ethical consumption among young consumers in Italy. Finally, implications and avenues for further research are discussed.